RUMAH PRODUKTIF (SEJAHTERA) BAGI MASYARAKAT TANPA PEKERJAAN (The Productive House for Jobless People) - Arief Sabaruddin; Lya Meilani; Titi Utami E.R (Unika Soegijapranata Semarang, 2015)
The basic function of house has as place for growth and development of family. The terminology of the decent house is not only limited to the physical aspect but also to be proper on the social, cultural and economic (non-physical aspects). The definition of house as a place that support a welfare of the occupant is not reached yet. The high rates of the unemployment in Indonesia, from the standpoint of housing shows that the function of house is not optimized yet. It have not been find a concept of productive house base on the culture gotong-royong is the the main problem in this research.This study aims to explore the concept of home and housing provision that can improve the welfare of its inhabitants. The research method is to conduct exploration analysis approach concepts and values of the family home as development human aspect of environmental, social, and economic. The results of the study is the concept of a productive house model.